Applications and Science in Soft Computing - Lotfi, Ahamad; Garibaldi, Jonathan M. (Springer Berlin Heidelberg, 2004)
The book covers the theory and application of soft computing techniques namely; neural networks, fuzzy logic, evolutionary computing and complex systems. The book is a collection of selected, edited papers presented at the 4th conference RACS Recent Advances in Soft Computing held in Nottingham, December 2002. It provides the latest developments in applications of soft computing techniques as well as advances in theoretical aspects of soft computing
Keywords: Computer Science; Artificial Intelligence (incl. Robotics); Appl.Mathematics/Computational Methods of Engineering; Applications of Mathematics; Operation Research/Decision Theory; IT in Business; Computer science; Operations research; Decision making; Information technology; Business / Data processing; Artificial intelligence; Applied mathematics; Engineering mathematics; Soft Computing